The effects of webcams on German neonatal intensive care units - study protocol of a randomised crossover trial (Neo-CamCare) - Nadine Scholten; Sebastian Bretthauer; Kerstin Eilermann; Anna Hagemeier; Martin Hellmich; Jan Hoffmann; Dirk Horenkamp-Sonntag; Christiane Jannes; Ludwig Kuntz; Pauline Mantell; Laura Mause; Andreas Müller; et al. (BMC, 2021)
Abstract Background The separation of parents and their prematurely born children during care in a neonatal intensive care unit (NICU) can have far-reaching consequences for the well-being of the parents and also of the children. The aim of this study is to evaluate the use of webcams on NICUs and to conduct a systematic assessment of their possible effects on parents and clinical staff. In addition, it aims at determining the need for webcams  in German NICUs and to identify possible barriers and moderators. The development and evaluation of practical guidance for the use of webcams will enable the comprehensive education of clinical staff and parents and, as a result, is intended to mitigate any potential undesirable consequences. Methods The study will be based on a mixed methods approach including all groups concerned in the care. Qualitative data will be collected in interviews and focus groups and evaluated using content analysis. The collection of quantitative data will be based on written questionnaires and will aim to assess the status quo as regards the use of webcams on German NICUs and the effects on parents, physicians, and nursing staff. These effects will be assessed in a randomised cross-over design. Four NICUs will be involved in the study and, in total, the parents of 730 premature babies will be invited to take part in the study. The effects on the nursing staff, such as additional workload and interruptions in workflows, will be evaluated on the basis of observation data. Discussion This study will be the largest multicentre study known to us that systematically evaluates the use of webcams in neonatal intensive care units. The effects of the  implementation of webcams on both parents and care providers will be considered. The results provide evidence to decide whether to promote the use of webcams on NICUs or not and what to consider when implementing them. Trial registration The trial has been registered at the German Clinical Trial Register (DRKS). Number of registration: DRKS00017755 , date of registration: 25.09.2019,